2015
DOI: 10.1007/s12035-015-9301-4
|View full text |Cite
|
Sign up to set email alerts
|

Anti-amyloid Aggregation Activity of Natural Compounds: Implications for Alzheimer’s Drug Discovery

Abstract: Several plant-derived natural compounds are known to exhibit anti-amyloid aggregation activity which makes them attractive as potential therapies to treat Alzheimer's disease. The mechanisms of their anti-amyloid activity are not well known. In this regard, many natural compounds are known to exhibit direct binding to various amyloid species including oligomers and fibrils, which in turn can lead to conformational change in the beta-sheet assembly to form nontoxic aggregates. This review discusses the mechanis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
55
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 83 publications
(55 citation statements)
references
References 121 publications
(133 reference statements)
0
55
0
Order By: Relevance
“…It is notable that many promising AD drug candidates are natural compounds, implying that not only medicinal inorganic chemistry but also natural compound chemistry is currently thriving within the AD area. Only a few examples will be mentioned as this area has been reviewed extensively [17,568,570,[632][633][634].…”
Section: Multifunctional Natural Compounds Against Admentioning
confidence: 99%
“…It is notable that many promising AD drug candidates are natural compounds, implying that not only medicinal inorganic chemistry but also natural compound chemistry is currently thriving within the AD area. Only a few examples will be mentioned as this area has been reviewed extensively [17,568,570,[632][633][634].…”
Section: Multifunctional Natural Compounds Against Admentioning
confidence: 99%
“…Drugs in clinical trials that decrease the levels of Ab 42 have been proposed to be linked to a reduced risk of the AD development (see, for example, refs. [36][37][38][39][40][41] ). Various experimental studies have shown that Ab 42 possesses an increased toxicity in comparison with other Ab segments.…”
Section: Introductionmentioning
confidence: 99%
“…Aging is the main risk factor associated with AD, and the prevalence of the disease has been estimated from 0.6% to 8.4% in people at ages between 65 and 85 years 3. Clinical features of this neurodegenerative condition include slow loss of memory and reasoning skills, speech abnormalities, and disorientation 35. The disease culminates in the complete custodial care of the patient and finally death, which is usually caused by pneumonia 3.…”
Section: Introductionmentioning
confidence: 99%